2015
DOI: 10.2174/1568026614666141216100907
|View full text |Cite
|
Sign up to set email alerts
|

Triplet Excited States as a Source of Relevant (Bio)Chemical Information

Abstract: Triplet excited states exhibit strongly medium-dependent properties, which turns them into valuable tools to probe the microenvironments existing in protein binding Finally, protein encapsulation can also modify the photoreactivity of the guest. This is illustrated by presenting an example of retarded photooxidation. 2 Graphical abstractKeywords: 1-acid glycoproteins, drug, laser flash photolysis, serum albumins, protein binding, transient absorption spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The properties of triplet excited states result to be markedly medium-dependent; in this context, they can be excellent reporters to investigate compartmentalized microenvironments, including the protein binding pockets. [14]. We have previously shown that the behavior of triplet excited states of ligands within transport proteins (such as1-acid glycoproteins or serum albumins), monitored by transient absorption spectroscopy, constitutes a powerful tool to examine drug binding.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of triplet excited states result to be markedly medium-dependent; in this context, they can be excellent reporters to investigate compartmentalized microenvironments, including the protein binding pockets. [14]. We have previously shown that the behavior of triplet excited states of ligands within transport proteins (such as1-acid glycoproteins or serum albumins), monitored by transient absorption spectroscopy, constitutes a powerful tool to examine drug binding.…”
Section: Introductionmentioning
confidence: 99%